2023
DOI: 10.3390/jcm12134347
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Physical Activity and Inactivity on Cardiovascular Risk across Women’s Lifespan: An Updated Review

Abstract: Physical inactivity (PI) represents a significant, modifiable risk factor that is more frequent and severe in the female population worldwide for all age groups. The physical activity (PA) gender gap begins early in life and leads to considerable short-term and long-term adverse effects on health outcomes, especially cardiovascular (CV) health. Our review aims to highlight the prevalence and mechanisms of PI across women’s lifespan, describing the beneficial effects of PA in many physiological and pathological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 181 publications
(199 reference statements)
1
10
0
Order By: Relevance
“…The beneficial effects of physical activity were irrespective of age and gender, thereby making it a universally applicable therapeutic modality for individuals with preexisting CVD. However, it is worth noting that women have lower rates of physical activity than men given that women are more subject to disparities arising from sociocultural, sociocultural and political factors [ 98 , 99 ]. Furthermore, this disparity is more prevalent in countries where social, cultural or religious norms restrict women from participating in physical activity [ 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of physical activity were irrespective of age and gender, thereby making it a universally applicable therapeutic modality for individuals with preexisting CVD. However, it is worth noting that women have lower rates of physical activity than men given that women are more subject to disparities arising from sociocultural, sociocultural and political factors [ 98 , 99 ]. Furthermore, this disparity is more prevalent in countries where social, cultural or religious norms restrict women from participating in physical activity [ 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the role of obesity in heart failure has been analyzed in depth, revealing that it is more frequently associated with HFpEF than with HFrEF. Furthermore, obesity has an important role as a greater risk factor in women than in men because it is associated with a sedentary lifestyle and reduced physical activity and also because of the inflammatory response associated with the visceral obesity of menopause [29][30][31]. The reason for the relationship between obesity and HFpEF appears to be due to some enhancement in its metabolic processes: insulin resistance is responsible for a systemic inflammatory state that leads to concentric cardiac remodeling [31,32].…”
Section: Obesitymentioning
confidence: 99%
“…Furthermore, obesity has an important role as a greater risk factor in women than in men because it is associated with a sedentary lifestyle and reduced physical activity and also because of the inflammatory response associated with the visceral obesity of menopause [29][30][31]. The reason for the relationship between obesity and HFpEF appears to be due to some enhancement in its metabolic processes: insulin resistance is responsible for a systemic inflammatory state that leads to concentric cardiac remodeling [31,32]. Increased LDL deposition and oxidized fatty acid increase vascular oxidative stress, causing an endothelial damage drive leading to an increased vascular tone and microcirculatory vasoconstriction.…”
Section: Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…Delivering physical exercise or physical activity may not only improve depression severity, but also directly tackle the constitutive elements of cardiovascular risk [ 20 ]. Several investigations have suggested that muscle strength is a plausible mechanism for these associations, as it has a protective effect on the development of CVD [ 20 , 21 , 22 , 23 ]. Also, both dynapenia (muscle weakness) and depressive symptoms are common in the elderly population [ 24 ], although women seem to live longer and have more years free of dynapenia than men [ 25 ].…”
Section: Introductionmentioning
confidence: 99%